ISLAM DAN PENDIDIKAN MULTIKULTURAL - Sobri Sobri (Institut Daarul Qur'an Jakarta, Indonesia, 2021)
This study aims to determine the view that multicultural education in Islamic education has been taught, so that the relationship between humans and other humans cannot be separated. This research method is a library research method, namely a method of reviewing written data both books, literature and notes that have a correlation with the discussion. This study uses a descriptive-analytic method, which uses existing sources, then describes them, then analyzes the correlation between Islamic education and multicultural education. The results of this study conclude that education is a process of training and teaching, coaching, training, teaching through teaching and training efforts. Islam sees that education is the most strategic means of uplifting human dignity in various fields of life and implies that there are three dimensions in an effort to develop human life, namely: the dimension of worldly life, the dimension of ukhrawi life, the dimension of the relationship between worldly life and ukhrawi. Multicultural education must support the main principles in eradicating cliché views of race, culture and religion.